'Fair Work' and the Modernization of Australian Labour Standards: A Case of Institutional Plasticity Entrenching Deepening Wage Inequality. (9th November 2016) - Buchanan, John; Oliver, Damian
Abstract: Australia was long recognized for its relatively compressed wage structure. From the 1940s to the 1970s this was associated with a comprehensive regime of 'award‐based' minimum wages. Since the 1980s, this has been subjected to comprehensive 'modernization'. After three decades of reform and in the most supportive economic environment in the OECD, Australian wage inequality has deepened. Although multiple political‐economic forces have been at play, the evolution of Australia's labour standards regime is an example of 'institutional plasticity' whereby the purpose and operations of wage‐setting institutions not only evolves but can actually be inverted over time.